Method for preparing hydrogen sulfide delivery nanoparticles for treating osteoporotic fractures

By doping zinc sulfide in the osteopsis osteopsis-8 and using bone targeting peptide to modify technology, the targeted delivery of hydrogen sulfide is delivered to nano-particle particles, which solves exogenous hydrogen sulfide to treat serum sulfur when treating osteoporosis fractures The problem of rising hydrogen levels achieves the effect of fracture healing and delayed bone loss.

CN119367554APending Publication Date: 2025-01-28THE FIRST AFFILIATED HOSPITAL OF SOOCHOW UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411459160.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, the use of exogenous hydrogen sulfide to treat osteoporotic fractures can easily lead to an increase in serum hydrogen sulfide levels and lack targeted delivery capabilities, resulting in side effects and limited fracture healing promotion effects.

Method used

Zinc sulfide formed by zinc ion and sulfur sulfur ions is doped in the lymidazole-8 of the amporogy-8, and uses bone targeting peptide to modify the technology to prepare a hydrogen sulfide with targeted delivery capacity Hydrogen is effectively released in the bone tissue without raising the level of hydrogen sulfide.

Benefits of technology

A targeted delivery of hydrogen sulfide in the bone tissue, promoting the healing of osteoporosis fractures, delaying bone loss, and avoiding the elevation of serum hydrogen sulfide levels, reducing the side effects of drugs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119367554A_ABST
    Figure CN119367554A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of hydrogen sulfide delivery nanoparticles, and relates to the technical field of drug delivery. The hydrogen sulfide delivery nanoparticle is used for treating osteoporotic fracture, and the preparation method comprises the following steps: uniformly mixing a first solution and a second solution to form a first mixed solution, the first solution containing a zinc source, and the second solution containing a sulfur source; uniformly mixing the first mixed solution with a 2-methylimidazole solution to form a second mixed solution, and preparing to obtain ZIF-H2S nanoparticles; bone targeting peptide is dissolved in water and diluted to form a peptide solution, and the bone targeting peptide contains sulfydryl; and adding the ZIF-H2S nanoparticles into the peptide solution to form a third mixed solution, uniformly mixing, and sequentially carrying out centrifugal treatment and washing treatment to prepare the hydrogen sulfide delivery nanoparticles. The prepared hydrogen sulfide delivery nanoparticles can be accurately delivered to the osteoporotic fracture, so that healing of the osteoporotic fracture is promoted, bone loss is delayed, and meanwhile, the level of hydrogen sulfide in serum cannot be increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of drug delivery, and in particular relates to a method for preparing hydrogen sulfide delivery nanoparticles for treating osteoporotic fractures. Background Art

[0002] Osteoporotic fracture (OPF) is a serious consequence of osteoporosis and one of the main causes of disability and death in the elderly. There are problems of bone loss and impaired bone regeneration in OPF, which leads to prolonged fracture healing time and a high incidence of refracture. Surgical treatment cannot prevent further bone loss in OPF, so systemic treatment is essential to reduce OPF recurrence and promote long-term survival of OPF patients. Current anti-osteoporosis drugs, such as bisphosphonates, denosumab, raloxifene, strontium ranelate, and teriparatide, have been shown to prevent OPF recurrence. However, these drugs lack targeted delivery capabilities and have significant side effects. In addition, most of these drugs work through a single mechanism. Although they can increase bone mass in patients, their effects on promoting fracture healing are very limited.

[0003] Hydrogen sulfide (H2S) is widely present in the normal human body and is considered to be the third endogenous gaseous transmitter after nitric oxide and carbon monoxide. H2S has a wide range of effects on various cellular components in the bone tissue microenvironment, promoting osteoblast differentiation, inhibiting osteoclast differentiation, and regulating macrophage polarization. Although H2S has great therapeutic potential, its narrow therapeutic window limits its clinical application. The release of H2S from commonly used H2S donors is uncontrollable, and even low-dose application can lead to potential toxic effects. In addition, most current exogenous H2S treatments inevitably increase serum H2S levels, which raises safety issues.

[0004] Therefore, it is crucial to prepare a drug that can be used to treat osteoporotic fractures and slow bone loss without causing an increase in serum hydrogen sulfide levels. Summary of the invention

[0005] One object of the present invention is to provide a method for preparing hydrogen sulfide delivery nanoparticles for treating osteoporotic fractures, so as to solve the technical problem in the prior art that using exogenous hydrogen sulfide to treat osteoporotic fractures easily leads to increased serum hydrogen sulfide levels.

[0006] Another object of the present invention is to further improve the targeting of hydrogen sulfide delivery nanoparticles.

[0007] According to the purpose of the present invention, the present invention provides a method for preparing hydrogen sulfide delivery nanoparticles for treating osteoporotic fractures, comprising the following steps:

[0008] Mixing a first solution and a second solution uniformly to form a first mixed solution, wherein the first solution contains a zinc source and the second solution contains a sulfur source;

[0009] The first mixed solution is mixed evenly with the 2-methylimidazole solution to form a second mixed solution, and ZIF-H2S nanoparticles are prepared;

[0010] dissolving a bone-targeting peptide in water to form a peptide solution after dilution, wherein the bone-targeting peptide contains a thiol group;

[0011] The ZIF-H2S nanoparticles are added to the peptide solution to form a third mixed solution, and after being evenly mixed, centrifugation and washing are performed in sequence to prepare hydrogen sulfide delivery nanoparticles.

[0012] Optionally, the molar concentration ratio of the sulfur source to the zinc source in the first mixed solution is any value in the range of 1:50-1:80.

[0013] Optionally, the molar concentration ratio of the zinc source in the second mixed solution to the 2-methylimidazole in the 2-methylimidazole solution is any value in the range of 1:50-1:80.

[0014] Optionally, the sulfur source is any one of sodium hydrosulfide or potassium sulfide.

[0015] Optionally, the zinc source is any one of zinc nitrate, zinc chloride or zinc acetate.

[0016] Optionally, the concentration of the ZIF-H2S nanoparticles in the third mixed solution is any value in the range of 2.0 mg / mL-4.0 mg / mL.

[0017] Optionally, in the step of uniformly mixing the first mixed solution with the 2-methylimidazole solution to form a second mixed solution to prepare ZIF-H2S nanoparticles, the preparation method further comprises the following steps:

[0018] The first mixed solution is added dropwise into the 2-methylimidazole solution, and after being evenly mixed, the mixture is sequentially resuspended, stirred, washed and centrifuged to prepare the ZIF-H2S nanoparticles.

[0019] Optionally, the concentration of the peptide solution is any value in the range of 0.05 mg / mL-0.2 mg / mL.

[0020] The present invention utilizes bone-targeted peptides to deliver exogenous zinc sulfide to osteoporotic fractures, and hydrogen sulfide delivery nanoparticles form hydrogen sulfide and zinc ions in the lysosomes within cells. The synergistic effect of hydrogen sulfide and zinc ions is utilized to achieve targeted delivery of zinc sulfide, which can promote the healing of osteoporotic fractures, delay bone loss, and avoid an increase in serum hydrogen sulfide levels.

[0021] Furthermore, the molar concentration ratio of the zinc source in the second mixed solution of the present invention to the 2-methylimidazole in the 2-methylimidazole solution is any value in the range of 1:50-1:80, that is, the excess zinc ions in the first mixed solution can be further chelated with 2-methylimidazole to form ZIF-H2S nanoparticles containing zinc ions on the surface, and the zinc ions on the surface of the ZIF-H2S nanoparticles are connected to the thiol groups in the bone targeting peptide to modify the bone targeting peptide to the surface of the ZIF-H2S nanoparticles to form hydrogen sulfide delivery nanoparticles with a targeted effect, thereby ensuring the binding stability of the ZIF-H2S nanoparticles and the bone targeting peptide, thereby improving the targeting of the hydrogen sulfide delivery nanoparticles.

[0022] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Hereinafter, some specific embodiments of the present invention will be described in detail in an exemplary and non-limiting manner with reference to the accompanying drawings. The same reference numerals in the accompanying drawings indicate the same or similar components or parts. It should be understood by those skilled in the art that these drawings are not necessarily drawn to scale. In the accompanying drawings:

[0024] Figure 1 is a schematic flow chart of a method for preparing hydrogen sulfide delivery nanoparticles according to one embodiment of the present invention;

[0025] Figure 2 The scanning electron microscopy and transmission electron microscopy images of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles;

[0026] Figure 3 Energy dispersive X-ray spectrometer images of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles;

[0027] Figure 4 Dynamic light scattering test graphs of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles;

[0028] Figure 5It is the Zeta potential detection diagram of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles;

[0029] Figure 6 X-ray photoelectron spectra of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles;

[0030] Figure 7 The total amount of surface peptides grafted on the surface of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in PBS (pH = 7.4) was directly detected by BCA method;

[0031] Figure 8 The total peptide loading of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in PBS (pH = 7.4) was directly detected by the BCA method;

[0032] Fig. 9 Schematic diagram of detecting the HS- content in ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles using the methylene blue method, and the release of hydrogen sulfide by ZIF-H2S-SDSSD in PBS with different pH values;

[0033] Fig.10 is a schematic diagram of the live-dead staining results of co-culture of 20 μg / mL nanoparticles with BMMs and BMSCs for 24 hours and 72 hours;

[0034] Fig.11 ALP staining images of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles co-cultured with BMSCs for 7 days and ARS staining images of co-cultured with BMSCs for 14 days;

[0035] Fig.12 is the percentage of ALP-positive area after co-culture of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles with BMSCs for 7 days;

[0036] Fig.13 is the OD value of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles co-cultured with BMSCs for 7 days;

[0037] Fig.14 are TRAP staining and F-actin staining images of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles co-cultured with BMMs for 5 days;

[0038] Fig.15 is the relative F-actin ring area percentage of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles co-cultured with BMMs for 5 days;

[0039] Fig.16 is the relative TRAP-positive area percentage of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles co-cultured with BMMs for 5 days;

[0040] Fig.17 It is the fluorescence imaging image of the main organs after intravenous injection of Cy7-labeled ZIF-H2S and ZIF-H2S-SDSSD nanoparticles;

[0041] Fig.18 The fluorescence intensity diagram of the main organs 12 hours after intravenous injection of Cy7-labeled ZIF-H2S and ZIF-H2S-SDSSD nanoparticles;

[0042] Fig.19 The fluorescence intensity diagram of the main organs 24 hours after intravenous injection of Cy7-labeled ZIF-H2S and ZIF-H2S-SDSSD nanoparticles;

[0043] Fig. 20 is the change of hydrogen sulfide content in bone tissue after intravenous injection of ZIF-H2S and ZIF-H2S-SDSSD nanoparticles;

[0044] Fig.21 is the change of serum hydrogen sulfide content after intravenous injection of ZIF-H2S and ZIF-H2S-SDSSD nanoparticles;

[0045] Fig. 22 It is the Micro-CT images of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in treating osteoporotic fracture callus;

[0046] Fig.23 It is the callus index of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporotic fractures;

[0047] Fig.24 is the bone volume fraction of osteoporotic fracture callus treated with ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles;

[0048] Fig.25These are the hematoxylin & eosin (H&E), Masson and TRAP staining images of osteoporotic fracture callus treated with ZIF, ZIF-SDSSD, ZIF-H2S and ZIF-H2S-SDSSD nanoparticles;

[0049] Fig.26 is the ratio of callus area to total area of ​​osteoporotic fractures treated with ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles;

[0050] Fig. 27 is the ratio of the new area to the total area of ​​osteoporotic fractures treated with ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles;

[0051] Fig.28 is the ratio of TRAP-positive area to total area in osteoporotic fracture callus treated with ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles;

[0052] Fig.29 These are the immunofluorescence and immunohistochemistry images of osteoporotic fracture callus treated with ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles;

[0053] Fig.30 It is F4 / 80 of ZIF, ZIF-SDSSD, ZIF-H2S, ZIF-H2S-SDSSD nanoparticles for the treatment of osteoporotic fracture callus + / CD86 - Cell content;

[0054] Fig.31 It is F4 / 80 of ZIF, ZIF-SDSSD, ZIF-H2S, ZIF-H2S-SDSSD nanoparticles for the treatment of osteoporotic fracture callus + / CD206 - Cell content;

[0055] Fig.32 It is the 1L-1β positive area content of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporotic fracture callus;

[0056] Fig.33 It is the 1L-10 positive area of ​​ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporotic fracture callus;

[0057] Fig.34 It is the Micro-CT images of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles for the treatment of osteoporosis;

[0058] Fig.35 is the bone volume fraction of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles for osteoporosis treatment;

[0059] Fig.36 is the bone area fraction of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles for osteoporosis treatment;

[0060] Fig.37 is the number of trabecular bones in osteoporosis treated with ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles;

[0061] Fig.38 It is the trabecular separation degree of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles for the treatment of osteoporosis;

[0062] Fig.39 These are H&E staining, Masson staining, and TRAP staining images of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles for the treatment of osteoporosis;

[0063] Fig.40 is the ratio of trabecular bone area to total area of ​​ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporosis;

[0064] Fig.41 is the ratio of the new bone area to the total area of ​​ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporosis;

[0065] Fig.42 It is the ratio of TRAP positive area to total area of ​​ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporosis. DETAILED DESCRIPTION

[0066] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0067] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. It is to be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only some structures related to the present application are shown in the accompanying drawings, rather than all structures. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0068] The terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.

[0069] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0070] In particular, the present invention provides a method for preparing hydrogen sulfide delivery nanoparticles, which are used for the treatment of osteoporotic fractures. It should be noted that hydrogen sulfide has a wide range of effects on various cell components in the bone tissue microenvironment, promotes osteoblast differentiation, inhibits osteoclast differentiation, and regulates macrophage polarization, and has great therapeutic potential in the field of bone disease treatment. However, its narrow treatment window limits clinical application, that is, the hydrogen sulfide released by commonly used hydrogen sulfide donors is uncontrollable, and even low-dose application can lead to potential toxic effects. In addition, most current exogenous hydrogen sulfide treatments inevitably increase serum hydrogen sulfide levels, thereby causing safety issues. In view of this, the inventors have made a lot of attempts, for example, using different hydrogen sulfide donors to deliver hydrogen sulfide, or using hydrogen sulfide donors in combination with bone-targeted peptides to deliver hydrogen sulfide. Although the above methods can introduce exogenous hydrogen sulfide into the body, at the same time, the serum hydrogen sulfide concentration is significantly increased.

[0071] By chance, the inventors discovered that by doping zinc sulfide formed by chelating zinc ions and sulfur source ions into zeolite imidazolate framework-8 and further modifying the bone-targeted peptide, the healing of osteoporotic fractures can be promoted without increasing the level of serum hydrogen sulfide. At the same time, it can delay bone loss and prevent the occurrence of re-fractures.

[0072] Figure 1 A schematic flow chart of a method for preparing hydrogen sulfide delivery nanoparticles according to one embodiment of the present invention is shown.

[0073] like Figure 1 As shown, the present invention provides a method for preparing hydrogen sulfide delivery nanoparticles for treating osteoporotic fractures, the preparation method comprising the following steps:

[0074] Step S100: uniformly mixing the first solution and the second solution to form a first mixed solution, wherein the first solution contains a zinc source and the second solution contains a sulfur source;

[0075] Step S200: the first mixed solution and the 2-methylimidazole solution are mixed evenly to form a second mixed solution, so as to prepare ZIF-H2S nanoparticles;

[0076] Step S300: dissolving the bone-targeting peptide in water to form a peptide solution through dilution, wherein the bone-targeting peptide contains a thiol group;

[0077] Step S400: adding ZIF-H2S nanoparticles to the peptide solution to form a third mixed solution, mixing the mixture evenly, and then centrifuging and washing the mixture in sequence to obtain hydrogen sulfide delivery nanoparticles.

[0078] In this embodiment, a first solution containing a zinc source and a second solution containing a sulfur source are first mixed to prepare a first mixed solution, wherein the first mixed solution includes a zinc sulfide precipitate and an excess zinc ion solution, and the excess zinc ions in the first mixed solution are chelated with 2-methylimidazole in the 2-methylimidazole solution and doped with the zinc sulfide precipitate and 2-methylimidazole to form ZIF-H2S nanoparticles, that is, the ZIF-H2S nanoparticles include zinc sulfide precipitate and zinc ions chelated with 2-methylimidazole. The zinc ions in the ZIF-H2S nanoparticles are coordinated and connected with the thiol group of the bone-targeted peptide in the peptide solution to form hydrogen sulfide delivery nanoparticles. Here, the first solution, the 2-methylimidazole solution, and the solvent used to dilute the peptide solution are all methanol reagents.

[0079] In this embodiment, the zinc ion content in the first solution is higher than the sulfur source ion content in the second solution, so that after zinc sulfide precipitate is formed in the first mixed solution, the excess zinc ions are chelated with 2-methylimidazole in the 2-methylimidazole solution to form ZIF-H2S nanoparticles, and the zinc ions on the surface of the ZIF-H2S nanoparticles are connected to the thiol groups in the bone targeting peptide through chemical bonds, thereby modifying the bone targeting peptide to the surface of the ZIF-H2S nanoparticles to form hydrogen sulfide delivery nanoparticles.

[0080] In this embodiment, the hydrogen sulfide delivery nanoparticles contain zinc sulfide, ZIF and bone-targeted peptides, that is, ZIF is used to chelate with zinc ions and zinc sulfide precipitates in the first mixed solution to form ZIF-H2S nanoparticles containing zinc sulfide precipitates inside and zinc ions modified on the surface, and the zinc ions on the surface of the ZIF-H2S nanoparticles are chemically bonded to the thiol groups of the bone-targeted peptides to modify the bone-targeted peptides on the surface of the ZIF-H2S nanoparticles, thereby forming hydrogen sulfide delivery nanoparticles. That is, the bone-targeted peptides are used to deliver exogenous zinc sulfide to the osteoporotic fracture, and the hydrogen sulfide delivery nanoparticles form hydrogen sulfide and zinc ions in the lysosomes in the cells, and the synergistic effect of hydrogen sulfide and zinc ions is used to achieve the directional delivery of zinc sulfide, promote the healing of osteoporotic fractures, and delay bone loss to prevent the recurrence of fractures.

[0081] In a further embodiment, the molar concentration ratio of the sulfur source and the zinc source in the first mixed solution is any value in the range of 1:50-1:80. In this embodiment, the molar concentration ratio of the sulfur source and the zinc source in the first mixed solution can be 1:50, 1:55, 1:60, 1:65, 1:70, 1:75 or 1:80, or any value in the range of 1:50-1:80. That is to say, when the molar concentration ratio of the sulfur source and the zinc source in the first mixed solution is within the above range, the sulfur source in the second solution can react with the zinc source in the first solution to form zinc sulfide precipitate, and the sulfur source ions are completely precipitated, ensuring that the sulfur source can be doped in 2-methylimidazole in the form of zinc sulfide precipitate, preventing the sulfur source ions from reacting incompletely to form hydrogen sulfide during the delivery process, thereby preventing the increase of serum hydrogen sulfide levels.

[0082] In a further embodiment, the molar concentration ratio of the zinc source in the second mixed solution to the 2-methylimidazole in the 2-methylimidazole solution is any value in the range of 1:50-1:80. In this embodiment, the molar concentration ratio of the zinc source in the second mixed solution to the 2-methylimidazole in the 2-methylimidazole solution can be 1:50, 1:55, 1:60, 1:65, 1:70, 1:75 or 1:80, or any value in the range of 1:50-1:80. In this embodiment, when the molar concentration ratio of the zinc source in the second mixed solution and the 2-methylimidazole in the 2-methylimidazole solution is within the above range, that is, the excess zinc ions in the first mixed solution can be further chelated with 2-methylimidazole to form ZIF-H2S nanoparticles having zinc ions on the surface, and the zinc ions on the surface of the ZIF-H2S nanoparticles are connected to the thiol groups in the bone targeting peptide to modify the bone targeting peptide to the surface of the ZIF-H2S nanoparticles to form hydrogen sulfide delivery nanoparticles with a targeted effect, thereby ensuring the binding stability of the ZIF-H2S nanoparticles and the bone targeting peptide, thereby improving the targeting of the hydrogen sulfide delivery nanoparticles.

[0083] In a further embodiment, the sulfur source is any one of sodium hydrosulfide or potassium sulfide. In the present embodiment, sodium hydrosulfide is used as a sulfur source, which has high reactivity and environmental friendliness, and is easily ionized into hydrosulfide ions in water. Hydrosulfide ions have high reactivity and can react rapidly with zinc ions to form zinc sulfide precipitates, thereby increasing the reaction rate of hydrogen sulfide delivery nanoparticles, and sodium hydrosulfide produces fewer by-products in the process of preparing zinc sulfide precipitates, and the pollution to the environment is relatively small. Potassium sulfide has a certain reaction controllability as a sulfur source. Potassium sulfide ionizes sulfur ions in water. When sulfur ions react with zinc ions, the generation rate and particle size of zinc sulfide can be controlled by adjusting the reaction conditions. In addition, the zinc sulfide precipitate prepared by potassium sulfide as a sulfur source has better stability.

[0084] In a further embodiment, the zinc source is any one of zinc nitrate, zinc chloride or zinc acetate. In this embodiment, the zinc source can be any one of zinc nitrate, zinc chloride or zinc acetate. Any zinc source reagent of zinc nitrate, zinc chloride or zinc acetate has good water solubility and is easily dissolved in a variety of solvents. The generated zinc ions have high reactivity and can quickly participate in chemical reactions and react with sulfur source ions to form zinc sulfide precipitation, thereby increasing the preparation rate of hydrogen sulfide delivery nanoparticles.

[0085] In a further embodiment, the concentration of ZIF-H2S nanoparticles in the third mixed solution is any value in the range of 2.0mg / mL-4.0mg / mL. In the present embodiment, the concentration of ZIF-H2S nanoparticles can be 2.0mg / mL, 2.5mg / mL, 3.0mg / mL, 3.5mg / mL or 4.0mg / mL, or any other value in 2.0mg / mL-4.0mg / mL. In other words, the concentration of ZIF-H2S nanoparticles in the third mixed solution is within the above range, which can ensure that ZIF-H2S nanoparticles maintain good dispersibility in the solution, avoid agglomeration or precipitation, so that the bone-targeted peptide can be uniformly and stably modified to the surface of ZIF-H2S nanoparticles, thereby significantly improving the stability, functionalization and biocompatibility of hydrogen sulfide delivery nanoparticles.

[0086] In a further embodiment, in step S200, the preparation method further includes the following steps:

[0087] The first mixed solution was added dropwise into the 2-methylimidazole solution, and after being evenly mixed, the mixture was resuspended, stirred, washed and centrifuged in sequence to prepare ZIF-H2S nanoparticles.

[0088] In this embodiment, in the process of preparing ZIF-H2S nanoparticles, the first mixed solution is added dropwise to the 2-methylimidazole solution, so that the zinc ions in the first mixed solution can be completely chelated with the 2-methylimidazole in the 2-methylimidazole solution, and the zinc sulfide precipitate in the first mixed solution is stably doped in the 2-methylimidazole. After the first mixed solution and the 2-methylimidazole solution are evenly mixed, they are sequentially resuspended, stirred, washed and centrifuged, so that the two solutions are fully contacted and gradually reacted during the mixing process, avoiding agglomeration or precipitation caused by excessive local concentration. The resuspension step can be The generated ZIF-H2S nanoparticles are ensured to be uniformly distributed in the solution to prevent them from settling due to gravity. The stirring process further promotes the full mixing and reaction of the reactants in the solution, which is conducive to the uniform generation of ZIF-H2S nanoparticles. The washing step is used to remove the unreacted substances, impurities and solvents attached to the surface of the ZIF-H2S nanoparticles, thereby improving the purity of the ZIF-H2S nanoparticles. The centrifugation step can effectively separate the ZIF-H2S nanoparticles from other components in the solution, thereby obtaining ZIF-H2S nanoparticles precipitated with uniform size, regular shape and high purity. Here, the solvent in the washing step is methanol reagent.

[0089] In a further embodiment, the concentration of the peptide solution is any value in the range of 0.05 mg / mL-0.2 mg / mL. In this embodiment, the concentration of the peptide solution can be 0.05 mg / mL, 0.1 mg / mL, 0.15 mg / mL or 0.2 mg / mL, or any value in the range of 0.05 mg / mL-0.2 mg / mL. That is, when the concentration of the peptide solution reacting with the ZIF-H2S nanoparticles is within the above range, the peptide molecules can more efficiently bind to the surface of the ZIF-H2S nanoparticles to form a stable modification layer to enhance the stability of the ZIF-H2S nanoparticles and prevent them from agglomerating, degrading or inactivating in the environment. A peptide solution concentration lower than 0.05 mg / mL will reduce the modification efficiency, and a peptide solution concentration higher than 0.2 mg / mL may result in unnecessary waste or have a negative impact.

[0090] The present application will be further described in detail below with reference to specific embodiments.

[0091] Example 1

[0092] First, 0.25 g of Zn(NO3)2·6H2O was dissolved in 1 mL of methanol to form a first solution, 56 mg of NaHS was dissolved in 10 mL of deionized water and diluted to 12.5 mM to form a second solution, and 1 ml of the first solution was added dropwise to the second solution to form a first mixed solution containing zinc sulfide precipitate and zinc ions. 2.8375 g of 2-methylimidazole was dissolved in 10 mL of methanol to form a 2-methylimidazole solution, and the first mixed solution was added dropwise to the 2-methylimidazole solution, stirred at room temperature for 30 min using a magnetic stirrer, and then centrifuged at a speed of 10,000 r / min for 5 min, the precipitate was collected and washed 3 times with methanol to obtain ZIF-H2S nanoparticles. 5 mg of bone-targeted peptide was dissolved in 0.5 ml of double-distilled water and gradiently diluted with methanol to 0.1 mg / mL to form a peptide solution. The prepared ZIF-H2S nanoparticles with a concentration of 3 mg / mL were resuspended in the peptide solution, magnetically stirred for 30 min, and centrifuged at 5000 r / min for 5 min. The precipitate was collected and washed 3 times with methanol to obtain hydrogen sulfide delivery nanoparticles, namely ZIF-H2S-SDSSD.

[0093] Comparative Example 1

[0094] The only difference between Comparative Example 1 and Example 1 is that the first mixed solution is the first solution, that is, the first mixed solution does not include a sulfur source, and the product prepared is ZIF-SDSSD.

[0095] Comparative Example 2

[0096] The only difference between Comparative Example 2 and Example 1 is that the peptide solution is a methanol solution, that is, the ZIF-H2S nanoparticles are mixed with the methanol solution to form the ZIF-H2S nanoparticles.

[0097] Comparative Example 3

[0098] The difference between Comparative Example 3 and Example 1 is that the final product formed is ZIF.

[0099] First, the nanoparticles prepared in Example 1 and Comparative Examples 1 to 3 were characterized. Figure 2 These are the scanning electron microscope and transmission electron microscope images of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles. Figure 3 Energy dispersive X-ray spectrometer images of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles. Figure 4 This is the dynamic light scattering test chart of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles. Figure 5This is the Zeta potential detection diagram of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles. Figure 6 It is the X-ray photoelectron spectrum of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles. Figure 7 The total amount of peptides grafted onto the surface of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in PBS (pH = 7.4) was directly detected by BCA method. Figure 8 The total peptide loading of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in PBS (pH = 7.4) was directly detected by BCA method. Fig. 9 It is a schematic diagram of detecting the HS- content in ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles using the methylene blue method, and the release of hydrogen sulfide by ZIF-H2S-SDSSD in PBS with different pH values.

[0100] like Figure 2 As shown, scanning electron microscopy images and transmission electron microscopy images show that ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles all have a dodecahedral morphology and a particle size of about 150 μm.

[0101] like Figure 3 As shown, the energy dispersive X-ray spectrometer graph shows that the N, O, Zn, and S elements are evenly distributed in ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles. Compared with ZIF, the S element in ZIF-SDSSD and ZIF-H2S nanoparticles is slightly increased, while the S element content in ZIF-H2S-SDSSD nanoparticles is the highest, indicating that the zinc sulfide precipitation is completely doped with 2-methylimidazole.

[0102] like Figure 4 and Figure 5 As shown, the dynamic light scattering test graph shows that the particle size of ZIF-H2S nanoparticles is similar to that of ZIF, while the particle size of ZIF-SDSSD and ZIF-H2S-SDSSD nanoparticles grafted with polypeptides is slightly increased, and the particle size distribution of each group of nanoparticles is relatively uniform. The Zeta potential detection graph shows that ZIF and ZIF-H2S nanoparticles are positive potential, while ZIF-SDSSD and ZIF-H2S-SDSSD after grafting polypeptides are negative potential, indicating that the bone targeting peptide is successfully grafted on the surface of ZIF and ZIF-H2S nanoparticles.

[0103] like Figure 6As shown, the X-ray photoelectron spectroscopy shows that ZIF and ZIF-H2S nanoparticles have no sulfur 2p high-resolution peak, while ZIF-SDSSD and ZIF-H2S-SDSSD nanoparticles after grafting polypeptides have sulfur 2p high-resolution peaks, indicating that ZIF-SDSSD and ZIF-H2S-SDSSD nanoparticles contain sulfur after grafting polypeptides.

[0104] like Figure 7 and Figure 8 As shown, the total loading amount of the peptide grafted on the surface of ZIF-H2S-SDSSD in PBS (pH = 7.4) was directly detected by the BCA method. After grafting the peptide, the content of the peptide in the ZIF-SDSSD and ZIF-H2S-SDSSD nanoparticles was significantly higher than that in the ZIF and ZIF-H2S nanoparticles, proving that the peptide was successfully grafted on the surface of the nanoparticles.

[0105] like Fig. 9 As shown, sodium hydrosulfide solutions of different concentrations were prepared, and the content of HS- was detected by the methylene blue method to establish a standard curve. The nanoparticles were directly reacted with the strong acidic detection solution, confirming that only ZIF-H2S and ZIF-H2S-SDSSD nanoparticles contained HS-. ZIF-H2S-SDSSD nanoparticles were dispersed in 10 mL of PBS with different pH values ​​(4.7, 5.8 and 7.4). In the PBS solution of pH = 7.4, ZIF-H2S-SDSSD basically did not release hydrogen sulfide. In the PBS solution of pH = 5.8, ZIF-H2S-SDSSD gradually released hydrogen sulfide. In the PBS solution of pH = 4.7, ZIF-H2S-SDSSD released hydrogen sulfide at a faster rate, proving that ZIF-H2S-SDSSD has the ability to release hydrogen sulfide in a pH-responsive manner.

[0106] The biocompatibility of the nanoparticles prepared in Example 1 and Comparative Examples 1 to 3 was further verified and analyzed. Fig.10 This is a schematic diagram of the live-dead staining results of co-culture of 20 μg / mL nanoparticles with BMMs (Bone Marrow-Derived Macrophages) and BMSCs (Bone Marrow Mesenchymal Stem Cells) for 24 hours and 72 hours.

[0107] like Fig.10 As shown, BMMs and BMSCs were incubated with 20 μg / mL nanoparticles for 24 hours and 72 hours, and then live-dead staining was performed. The results showed that no red fluorescent dead cells were observed in each group, confirming the biosafety of the nanoparticles at 20 μg / mL.

[0108] The regulatory effect of the nanoparticles prepared in Example 1 and Comparative Examples 1 to 3 on osteogenic differentiation was further verified and analyzed. Fig.11 The images are the alkaline phosphatase (ALP) staining of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles and BMSCs after co-culture for 7 days and Alizarin Red S (ARS) staining after co-culture for 14 days. Fig.12 is the percentage of ALP-positive area after co-culture of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles with BMSCs for 7 days, Fig.13 It is the OD (Optical density) value of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles co-cultured with BMSCs for 7 days.

[0109] like Figures 11 to 13 As shown, ALP staining of the nanoparticles in Example 1 showed that compared with the nanoparticles in Comparative Examples 1 to 3, the expression level of bone marker ALP of the ZIF-H2S-SDSSD composition in Example 1 was significantly increased, and ARS staining of the nanoparticles in Example 1 showed that compared with the nanoparticles in Comparative Examples 1 to 3, the calcium nodule formation of the ZIF-H2S-SDSSD in Example 1 was significantly increased, indicating that ZIF-H2S-SDSSD can promote the osteogenic differentiation of BMSCs.

[0110] The regulatory effect of the nanoparticles prepared in Example 1 and Comparative Examples 1 to 3 on osteoclast differentiation was further verified and analyzed. Fig.14 The images of tartrate-resistant acid phosphatase (TRAP) and F-actin staining after co-culture of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles with BMMs for 5 days. Fig.15 is the relative percentage of F-actin ring area after co-culture of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles with BMMs for 5 days, Fig.16 is the relative percentage of TRAP-positive area after co-culture of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles with BMMs for 5 days.

[0111] like Figures 14 to 16As shown in the figure, TRAP staining showed that compared with the control group, the formation of TRAP-positive osteoclasts in the ZIF-H2S-SDSSD group was significantly reduced, and F-actin staining showed that compared with the control group, the F-actin ring of osteoclasts in the ZIF-H2S-SDSSD group was smaller, indicating that ZIF-H2S-SDSSD can inhibit the osteoclast differentiation of BMMs.

[0112] The bone-targeted delivery capabilities of the nanoparticles prepared in Example 1 and Comparative Examples 1 to 3 were further verified and analyzed. Fig.17 These are the fluorescence imaging images of major organs after intravenous injection of Cy7-labeled ZIF-H2S and ZIF-H2S-SDSSD nanoparticles. Fig.18 This is the fluorescence intensity diagram of the main organs 12 hours after intravenous injection of Cy7-labeled ZIF-H2S and ZIF-H2S-SDSSD nanoparticles. Fig.19 This is the fluorescence intensity diagram of the main organs 24 hours after intravenous injection of Cy7-labeled ZIF-H2S and ZIF-H2S-SDSSD nanoparticles. Fig. 20 is the change of hydrogen sulfide content in bone tissue after intravenous injection of ZIF-H2S and ZIF-H2S-SDSSD nanoparticles, Fig.21 The changes in serum hydrogen sulfide content after intravenous injection of ZIF-H2S and ZIF-H2S-SDSSD nanoparticles.

[0113] like Figures 17 to 19 As shown, the fluorescence imaging results showed that the fluorescence signal of bone tissue in the ZIF-H2S-SDSSD group was significantly enhanced compared with the ZIF-H2S group without bone-targeting peptide grafting, indicating that the modification of bone-targeting peptide SDSSD promoted the enrichment of nanoparticles in bone tissue.

[0114] like Fig. 20 and Fig.21 As shown in the figure, the results of measuring the hydrogen sulfide content in serum and bone tissue by methylene blue method showed that the hydrogen sulfide levels in serum and bone tissue of ZIF-H2S group remained unchanged at 12 hours and 24 hours after injection. In contrast, the hydrogen sulfide level in bone tissue of ZIF-H2S-SDSSD group increased significantly at both time points, while the hydrogen sulfide level in serum remained stable, indicating that ZIF-H2S-SDSSD has the ability to deliver hydrogen sulfide to bone tissue in a targeted manner, effectively avoiding the potential toxic side effects of hydrogen sulfide.

[0115] Finally, the therapeutic effects of the nanoparticles prepared in Example 1 and Comparative Examples 1 to 3 on osteoporotic fractures were verified and analyzed. Fig. 22 Micro-CT images of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporotic fracture callus. Fig.23 It is the callus index of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporotic fractures. Fig.24 This is a bar graph of bone volume fraction of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporotic fracture callus. Fig.25 These are the hematoxylin & eosin (H&E), Masson and TRAP staining images of ZIF, ZIF-SDSSD, ZIF-H2S and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporotic fracture callus. Fig.26 The ratio of callus area to total area of ​​ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporotic fractures. Fig. 27 The ratio of the new area to the total area of ​​ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporotic fractures. Fig.28 is the ratio of TRAP positive area to total area in osteoporotic fracture callus treated with ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles. Fig.29 These are the immunofluorescence and immunohistochemistry images of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporotic fracture callus. Fig.30 It is F4 / 80 of ZIF, ZIF-SDSSD, ZIF-H2S, ZIF-H2S-SDSSD nanoparticles for the treatment of osteoporotic fracture callus + / CD86 - Cell content, Fig.31 It is F4 / 80 of ZIF, ZIF-SDSSD, ZIF-H2S, ZIF-H2S-SDSSD nanoparticles for the treatment of osteoporotic fracture callus + / CD206 - Cell content, Fig.32 The 1L-1β positive area content of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporotic fracture callus. Fig.33 It is the 1L-10 positive area of ​​ZIF, ZIF-SDSSD, ZIF-H2S, ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporotic fracture callus. Fig.34 Micro-CT images of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles for osteoporosis treatment. Fig.35is the bone volume fraction of ZIF, ZIF-SDSSD, ZIF-H2S, ZIF-H2S-SDSSD nanoparticles for osteoporosis treatment, Fig.36 The bone area fraction of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles for osteoporosis treatment. Fig.37 is the number of trabecular bone in the treatment of osteoporosis by ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles, Fig.38 The trabecular separation of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles for the treatment of osteoporosis. Fig.39 These are H&E staining, Masson staining, and TRAP staining images of ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporosis. Fig.40 is the ratio of trabecular area to total area of ​​ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporosis. Fig.41 is the ratio of the new bone area to the total area of ​​ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporosis. Fig.42 It is the ratio of TRAP positive area to total area of ​​ZIF, ZIF-SDSSD, ZIF-H2S, and ZIF-H2S-SDSSD nanoparticles in the treatment of osteoporosis.

[0116] like Figure 22 to Figure 25 As shown in the figure, the callus Micro-CT results showed that the callus index of the ZIF-H2S-SDSSD group increased significantly compared with the saline group on the 7th and 14th days after surgery, while the callus index of the ZIF-H2S-SDSSD group decreased significantly on the 28th day after surgery, but the femoral morphology was better, indicating that the callus remodeling and shaping period started earlier. The callus bone volume fraction (BV / TV) of the ZIF-H2S-SDSSD group was the highest at all three time points, indicating that ZIF-H2S-SDSSD effectively promoted the healing of osteoporotic fractures.

[0117] like Figure 26 to Figure 28As shown in the figure, H&E staining and Masson staining showed that on the 14th day after surgery, the ZIF-H2S-SDSSD group had the largest callus area and the most new bone formation. On the 28th day after surgery, compared with the saline group, the callus area of ​​the ZIF-H2S-SDSSD group was significantly reduced, but with better histological morphology, confirming that its callus remodeling and shaping period started earlier. Callus TRAP staining showed that compared with the saline group, the ZIF-H2S-SDSSD group had significantly fewer TRAP-positive osteoclasts, indicating that osteoclastogenesis was inhibited.

[0118] like Figure 29 to Figure 33 As shown, callus tissue immunofluorescence showed that on the 7th day after surgery, F4 / 80 in the ZIF-H2S-SDSSD group was higher than that in the normal saline group. + / CD86 + Cytopenia, F4 / 80 + / CD206 + The number of cells increased, indicating that ZIF-H2S-SDSSD promoted the reprogramming of M1 macrophages to M2 phenotype. Callus immunohistochemistry showed that on the 7th day after surgery, compared with the saline group, the expression of IL-1β in the ZIF-H2S-SDSSD group decreased, while the expression of IL-10 increased, indicating that ZIF-H2S-SDSSD alleviated the inflammatory microenvironment of the callus by regulating macrophage polarization.

[0119] like Figures 34 to 38 As shown in the figure, the Micro-CT results of trabecular bone under the distal femoral growth plate showed that 28 days after surgery, compared with the normal saline group, the BV / TV, bone area fraction (BS / TV), and trabecular number (Tb.N) of the ZIF-H2S-SDSSD group were significantly increased, and the trabecular separation (Tb.Sp) was significantly decreased, indicating that ZIF-H2S-SDSSD effectively alleviated bone loss.

[0120] like Figure 39 to Figure 42 As shown, H&E staining and Masson staining of trabecular bone under the distal femoral growth plate showed that 28 days after surgery, the ZIF-H2S-SDSSD group had more trabeculae and new bone compared with the saline group. TRAP staining of trabecular bone under the distal femoral growth plate showed that 28 days after surgery, the TRAP-positive osteoclasts in the ZIF-H2S-SDSSD group were significantly reduced compared with the saline group, indicating that ZIF-H2S-SDSSD can significantly improve osteoporosis while promoting fracture healing.

[0121] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0122] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing hydrogen sulfide delivery nanoparticles for treating osteoporotic fractures, characterized in that: The steps include: Mixing a first solution and a second solution uniformly to form a first mixed solution, wherein the first solution contains a zinc source and the second solution contains a sulfur source; The first mixed solution is mixed evenly with the 2-methylimidazole solution to form a second mixed solution, and ZIF-H2S nanoparticles are prepared; dissolving a bone-targeting peptide in water to form a peptide solution after dilution, wherein the bone-targeting peptide contains a thiol group; The ZIF-H2S nanoparticles are added to the peptide solution to form a third mixed solution, and after being evenly mixed, centrifugation and washing are performed in sequence to prepare hydrogen sulfide delivery nanoparticles.

2. The preparation method according to claim 1, characterized in that: The molar concentration ratio of the sulfur source to the zinc source in the first mixed solution is any value in the range of 1:50-1:

80.

3. The preparation method according to claim 2, characterized in that: The molar concentration ratio of the zinc source in the second mixed solution to the 2-methylimidazole in the 2-methylimidazole solution is any value in the range of 1:50-1:

80.

4. The preparation method according to claim 3, characterized in that: The sulfur source is any one of sodium hydrosulfide or potassium sulfide.

5. The preparation method according to claim 4, characterized in that: The zinc source is any one of zinc nitrate, zinc chloride or zinc acetate.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The concentration of the ZIF-H2S nanoparticles in the third mixed solution is any value in the range of 2.0 mg / mL-4.0 mg / mL.

7. The preparation method according to claim 6, characterized in that: The step of uniformly mixing the first mixed solution with the 2-methylimidazole solution to form a second mixed solution to prepare ZIF-H2S nanoparticles further includes the following steps: The first mixed solution is added dropwise into the 2-methylimidazole solution, and after being evenly mixed, the mixture is sequentially resuspended, stirred, washed and centrifuged to prepare the ZIF-H2S nanoparticles.

8. The preparation method according to claim 7, characterized in that: The concentration of the peptide solution is any value in the range of 0.05 mg / mL to 0.2 mg / mL.